Firm Size Drives Value in Indonesian Pharma, Intellectual Capital and Leverage : Ukuran Perusahaan Mendorong Nilai Perusahaan Farmasi Indonesia, Modal Intelektual dan Leverage - Eby Amelia Hariati; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2024)
This study analyzes how Intellectual Capital, Leverage, and Firm Size influence the value of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2021. Using numerical and secondary data analysis of 60 data points, the findings reveal that Firm Size significantly impacts company value, while Intellectual Capital and Leverage do not. Conducted with SPSS analysis, the results suggest that stakeholders should focus on Firm Size when evaluating pharmaceutical companies. The study is limited to the pharmaceutical sector and the 2016-2021 period, indicating a need for further research across different sectors and timeframes. Highlights: Firm Size Impact: Firm Size significantly influences pharmaceutical company value. Insignificant Factors: Intellectual Capital and Leverage do not affect company value. Future Research: Explore other sectors and timeframes for broader insights. Keywords: Intellectual Capital, Leverage, Firm Size, Pharmaceutical Companies, IDX